The Profile of Anticancer Activities of Sambiloto Extract (Andrographis paniculata Nees) from Several Locations in East Java - Roihatul Mutiah; Fina Luthfiana; Arief Suryadinata; Wirda Anggraini; Anik Listiyana (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2020)
Sambiloto (Andrographis paniculata Nees) contains andrographolid compound which has potentialas an anticancer. The difference of growth location has affected the distinction of metabolite content. Thisstudy aims to determine the profile of anticancer activities of A. paniculata extract from several locations inEast Java. The extracts from several locations were tested for activity on T47D cancer cell using MTT assaymethod. Thus, the result of this study describes that A. paniculata extract from several different locations doesnot provide significantly different anticancer activities with the amount of (p>0.05). The extracts which havemoderate anticancer activity were A. paniculata extracts from Selopuro Subdistrict Blitar Regency, SingosariSubdistrict Malang Regency, Lowokwaru Subdistrict Malang City, Klojen Subdistrict Malang City,Purwodadi Subdistrict Pasuruan Regency, Purwosari Subdistrict Pasuruan Regency, and PandaanSubdistrict Pasuruan Regency